2015
DOI: 10.1039/c5ay01246e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of 8-hydroxy-2′-deoxyguanosine as a biomarker for oxidative DNA damage in HEK293 cells exposed to 3-chloro-1,2-propanediol

Abstract: Detection of 8-hydroxy-2′-deoxyguanosine generated via ROS-mediated oxidative DNA damage in HEK293 cells through a fabricated electrochemical sensor for evaluation of the cytotoxicity of 3-MCPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Taken together, the data presented in this study are in agreement with the short-term (up to 48 hour) exposure studies performed in vitro with other cell lines (Buhrke et al, 2018;Liu et al, 2012;Ozcagli et al, 2016;Senyildiz et al, 2017;Sun et al, 2015) and further support the notion that 3-MCPD may be a mild toxin towards human proximal tubule cells. Moreover, no adverse kidney (or other) events among humans have been attributed to 3-MCPD-associated food consumption or occupational exposure ("3-CHLORO-1,2-PROPANEDIOL (JEC-FA Food Additives Series 48)," 2001) and a thorough toxicological evaluation in a non-human primate model showed hematological problems instead of any renal effects (Kirton et al, 1970).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Taken together, the data presented in this study are in agreement with the short-term (up to 48 hour) exposure studies performed in vitro with other cell lines (Buhrke et al, 2018;Liu et al, 2012;Ozcagli et al, 2016;Senyildiz et al, 2017;Sun et al, 2015) and further support the notion that 3-MCPD may be a mild toxin towards human proximal tubule cells. Moreover, no adverse kidney (or other) events among humans have been attributed to 3-MCPD-associated food consumption or occupational exposure ("3-CHLORO-1,2-PROPANEDIOL (JEC-FA Food Additives Series 48)," 2001) and a thorough toxicological evaluation in a non-human primate model showed hematological problems instead of any renal effects (Kirton et al, 1970).…”
Section: Discussionsupporting
confidence: 90%
“…A plethora of in vivo studies done mostly in rat models have demonstrated the potential for 3-MCPD to induce a variety of renal and other effects in acute and chronic settings ("3-CHLORO-1,2-PROPANEDIOL (JECFA Food Additives Series 48)," 2001; Cho et al, 2008b;Huang et al, 2018;Onami et al, 2014). In vitro renal studies, however, have only been done in rat NRK-52E and human HEK or TK cell models to confirm the short-term effects of 24 or 48 hour exposures (Buhrke et al, 2018;Liu et al, 2012;Ozcagli et al, 2016;Senyildiz et al, 2017;Sun et al, 2015). Since the kidneys are among the list of organs targeted by 3-MCPD, we sought to investigate both the short-and long-term effects of directly exposing this compound to human proximal tubule cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…subjects, respectively, thereby requiring sensitive methodologies for their assay [241,243]. The most commonly used analytical techniques for the detection of 8-OHdG in urine are high performance liquid chromatography-electrochemical detection (HPLC-ECD) [244], HPLC tandem mass spectrometry (HPLC MS/MS) [245], capillary electrophoresis with electrochemical detection (CE-ECD) [242,246], electrochemical methods including cyclic voltammetry (CV) [247][248][249], differential pulse voltammetry [250] and linear sweep voltammetry (LSV) [251]. Ultraviolet spectroscopy [252,253],…”
Section: Discussionmentioning
confidence: 99%
“…Electrochemical methodologies such as cyclic voltammetry (CV) and differential pulse voltammetry (DPV) for quantitative analysis of 8-OHdG have claimed subnanomolar detection sensitivities [247,250]. Similarly, spectroscopic methods such as ultraviolet-visible spectroscopy (UV-Vis) and fluorescence spectroscopy also have been explored for the detection of 8-OHdG [252][253][254] with subnanomolar and picomolar sensitivities.…”
Section: Comparison With Other Sensing Strategiesmentioning
confidence: 99%